2018
DOI: 10.14419/ijet.v7i2.4.13028
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of AODV protocol under sinkhole attack in wireless sensor network

Abstract: A Wireless Sensor Network (WSNs) is a collection of number of sensor nodes which are left open in an unsecured environment. Sensor nodes work and communicate together to attain the desired goals. They are placed at the locations where monitoring is otherwise impossible. Wireless Sensor Networks are resource constrained which may be computational power, memory capacity, battery power etc. As Wireless Sensor Networks are implemented in the unattended environment, they are prone to discrete type of security attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Sinkhole attacks: In this attack, a compromised IoT node or device broadcast false metrics about its capabilities to its neighboring nodes in order to attract these nodes to use it as a forwarding node (next hop) in their routing path [137]. The compromised node or device will attract so much traffic to it, then it drops these packets or inspect it and gain access to sensitive information [13,16,102,104,111,138].…”
Section: Network Layer Attacksmentioning
confidence: 99%
“…Sinkhole attacks: In this attack, a compromised IoT node or device broadcast false metrics about its capabilities to its neighboring nodes in order to attract these nodes to use it as a forwarding node (next hop) in their routing path [137]. The compromised node or device will attract so much traffic to it, then it drops these packets or inspect it and gain access to sensitive information [13,16,102,104,111,138].…”
Section: Network Layer Attacksmentioning
confidence: 99%
“…The presented method by using a trustable path confirms the honesty of the transferred messages. [55] analyzed the impact of Sinkhole attack on AODV protocol with varying number of attacker nodes. Simulated the proposed methodology in Qualnet 7.3.1 software using 50 nodes in an area of 1500 m x 1500 m with no mobility.…”
Section: Sink Hole Attackmentioning
confidence: 99%
“…They focused on techniques viz., cryptography, sequence number, hop count and mobile agent. They found that mainly techniques have security issues, high communication cost, low detection rate and high detection overheads Sehrawat et al (2018).…”
mentioning
confidence: 99%
“…They focused on techniques viz., cryptography, sequence number, hop count and mobile agent. They found that mainly techniques have security issues, high communication cost, low detection rate and high detection overheads Sehrawat et al (2018) [55]. analyzed the impact of Sinkhole attack on AODV protocol with varying number of attacker nodes.…”
mentioning
confidence: 99%